Spectrophotometric method for Determination of oxymetazoline, HCl in a Pharmaceutical formulation using 2,4 - dinitrophenylhydrazine - Israa Talib Humeidy (Tikrit Journal of Pure Science)
Rapid, sensitive and simple spectrophotometric method for the determination of oxymetazoline hydrochloride (OXMZ) is developed. The method is based on an oxidative coupling reaction with 2,4-dinitrophenylhydrazine (2,4-DNPH) in a basic medium (pH 11.2) in the presence of  potassium periodate to produce a green colour, soluble in water , stable product and absorbs at 607 nm. Beer's law was in the linear range 2.5-30 μg/ml of OXMZ, the molar absorptivity , Sandellʼs sensitivity index and detection limit were 7242 liter. mol-1.cm-1, 0.0409 μg.cm-2 and 0.1877 μg/ml respectively. The RSD value was 1.24- 1.39% depending on the concentration. This method was applied successfully to the determination of oxymetazoline in pharmaceutical preparation nazordin drops with recovery of not less than  99.87 % .